Who Participates in Tax Avoidance? - Annette Alstadsæter; Martin Jacob (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes the sources of heterogeneity in legal tax avoidance strategies across individuals. Three conditions are required for a taxpayer to participate in tax avoidance: incentive, access, and awareness. Using rich Swedish administrative panel data with a unique link between corporate and individual tax returns, we analyze individual participation in legal tax planning around the 2006 Swedish tax reform. Our results suggest that closely held corporations are utilized to facilitate income shifting across tax bases to reduce the individual's overall tax burden. We find that both tax incentives and awareness of tax incentives impact the decision to access income-shifting opportunities. Our results show that factors explaining participation in legal tax avoidance substantially differ from those explaining participation in illegal tax evasion.
Keywords: H20; H24; H25; H26; 330; tax avoidance; income shifting; income taxation; dividend taxation